1990
DOI: 10.1121/1.399729
|View full text |Cite
|
Sign up to set email alerts
|

Temporal integration in amplitude modulation detection

Abstract: Thresholds for detecting sinusoidal amplitude modulation (AM) of a wideband noise carrier were measured as a function of the duration of the modulating signal. The carrier was either; (a) gated with a duration that exceeded the duration of modulation by the combined stimulus rise and fall times; (b) presented with a fixed duration that included a 500-ms carrier fringe preceding the onset of modulation; or (c) on continuously. In condition (a), the gated-carrier temporal modulation transfer functions (TMTFs) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 15 publications
7
86
2
Order By: Relevance
“…In most cases, however, performance on psychophysical tasks improves with stimulus duration, be it absolute detection 17 , frequency discrimination 18 , modulation detection 19,20 or localization 21,22 . Discrimination of textures with distinct statistical properties also improved with duration (experiment 1), as did discrimination of the temporal detail of single sources (experiments 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, however, performance on psychophysical tasks improves with stimulus duration, be it absolute detection 17 , frequency discrimination 18 , modulation detection 19,20 or localization 21,22 . Discrimination of textures with distinct statistical properties also improved with duration (experiment 1), as did discrimination of the temporal detail of single sources (experiments 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…Thresholds were similar for both gated and continuous carrier conditions for modulation cycles greater than four. These results suggest that a difference in stimulus gating may have caused the absence of a critical duration effect in AM detection observed from the comparison of data from Sheft and Yost (1990) and Lee and Bacon (1997). For the gated carrier condition, shaping the onset/offset of stimuli with rise/fall times might reduce modulation information at the onset/offset, which might result in a dramatic change in threshold for a smaller number of modulation cycles.…”
Section: Introductionmentioning
confidence: 82%
“…There was a critical duration of four cycles of modulation in which a dramatic threshold improvement (more than factor of 2) was observed when the stimulus duration increased from a shorter duration to this critical duration; only a slight or no improvement of threshold was observed when the stimulus duration exceeded this critical duration for modulation rates of 10, 20, 40, and 80 Hz. Lee and Bacon (1997) compared AM detection data (Sheft and Yost, 1990) with their AM depth discrimination data and found that AM detection lacks the critical duration effect observed in AM depth discrimination. In contrast, AM detection thresholds were found to decrease gradually with increasing duration from 25 to 400 ms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations